2007
DOI: 10.1074/jbc.m606352200
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Hyaluronan Released in Sterile Injury Involves a Unique Receptor Complex Dependent on Toll-like Receptor 4, CD44, and MD-2

Abstract: Inflammation under sterile conditions is not well understood despite its importance in trauma and autoimmune disease. To investigate this process we established mouse models of sterile injury and explored the role of hyaluronan in mediating inflammation following injury. The response of cultured monocytes to hyaluronan was different than the response to lipopolysaccharide (LPS) despite both being dependent on Toll-like receptor 4 (TLR4). Cultured cells exposed to hyaluronan showed a pattern of gene induction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
326
3
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(348 citation statements)
references
References 51 publications
11
326
3
8
Order By: Relevance
“…It has also been reported that fragments of HA or HA at low molecular weight are able to interact with TLR-4 and CD44 receptors, thereby stimulating inflammation or increasing the inflammatory mechanism previously induced by other agents in different cell types [11][12][13][14][15][16]. Hence, the generation of lower molecular weight HA in pathologies may act as an endogenous danger signal, leading to the activation of both innate and acquired immunity.…”
Section: Page 4 Of 30mentioning
confidence: 99%
“…It has also been reported that fragments of HA or HA at low molecular weight are able to interact with TLR-4 and CD44 receptors, thereby stimulating inflammation or increasing the inflammatory mechanism previously induced by other agents in different cell types [11][12][13][14][15][16]. Hence, the generation of lower molecular weight HA in pathologies may act as an endogenous danger signal, leading to the activation of both innate and acquired immunity.…”
Section: Page 4 Of 30mentioning
confidence: 99%
“…Individual TLRs can recognize several structurally unrelated ligands. For example, TLR4 recognizes not only LPS but also taxol (Kawasaki et al, 2000), fusion (F) protein of respiratory syncytial virus (Kurt-Jones et al, 2000), extra domain A of fibronectin (Okamura et al, 2001), heat shock protein (HSP) 60 (Ohashi et al, 2000), HSP 70 (Habich et al, 2002), and hyaluronan (Taylor et al, 2004(Taylor et al, , 2007. It is important to understand how TLR4 recognizes these structurally unrelated ligands.…”
Section: Ligands Of Tlrsmentioning
confidence: 99%
“…Results and Discussion TLR4 signaling may be induced either by LPS or by endogenous GAG fragments derived from the breakdown of extracellular matrix components (10,11) (Fig. 1A).…”
mentioning
confidence: 99%
“…TLR4 signaling may be induced by two pathways (10,11). LPS represents the "classic" pathway, activating TLR4 signaling through interactions with the adapter protein, myeloid differentiation factor-88 (MyD88), LPS binding protein (LBP), CD14, and CXCR4 (12).…”
mentioning
confidence: 99%